Prevalence of Skeletal Malocclusions in relation to gender and pernicious oral habits: A Literature Review - Alvarez Barzola, Olga Pierina (2025)
The aesthetics of the smile are crucial in both personal and social perception. As a result, many patients seek orthodontic treatments primarily to improve the appearance of their smile, often overlooking proper occlusion. Therefore, this literature review aims to examine the factors influencing the development of skeletal malocclusions through lateral cephalometric radiographs and cephalometric analysis. Materials and Methods: A review of studies published between 2019 and 2023 was conducted, including books and scientific articles, using databases such as Scopus, PubMed, Web of Science, and SciELO. Results: Skeletal malocclusions, such as Class II and III, are prevalent in different regions of Latin America, with significant variations depending on the country and gender. Results from Cisneros' study (16) showed that Class II skeletal malocclusion is more common in females, at 61.90%, while Class I is more prevalent in males, at 52.63%. Conclusion: Cephalometric classification remains an essential tool for distinguishing between skeletal and dental malocclusions, providing a foundation for orthodontic treatment planning. The review concludes that, although the frequency and type of malocclusion may vary between genders, deforming habits are a key factor in the development of malocclusions. Understanding these factors is crucial for the prevention and treatment of dentomaxillary anomalies, emphasizing the need for a comprehensive approach in diagnosing and managing these conditions.